(untitled) (LEGAL DIALOGICA, 2025)
The purpose of this study is to determine and analyze the effectiveness of the police’s function in combating animal theft in Wajo Regency. It also aims to determine and analyze factors influencing the effectiveness of the police’s function in combating animal theft in Wajo Regency. This research is an empirical legal research, a legal research method that examines law in its concrete meaning and examines how it operates in the community. The data used in this study include primary data, data, and materials. The legal data collection techniques used in this study were interviews and questionnaires. The results of this study demonstrate that the effectiveness of the National Police (Polri) in combating animal theft in Wajo Regency has been quite effective, although there is still room for improvement. Future success depends heavily on stronger synergy between the police, local government, and the community in building a neighborhood security system based on prevention, monitoring, and rapid response to any potential disturbances, particularly in the livestock sector. Several key factors influence the effectiveness of the National Police’s function in handling animal theft in Wajo Regency, including infrastructure, technical competence of officers, community participation, local government support, geographic location, obstacles to legal evidence, and community legal culture. The police are expected to increase patrols in areas prone to animal theft. Furthermore, it is crucial to establish a task force or special team focused on handling animal theft crimes to facilitate faster and more effective investigations. Furthermore, the National Police are expected to be more active in building cooperation with the community through legal outreach activities and strengthening neighborhood security systems, with support from the local government. Abstrak : Tujuan penelitian ini untuk mengetahui dan menganalisis mengetahui dan menganalisis efektivitas fungsi polri dalam penanggulangan tindak pidana pencurian hewan di Kabupaten Wajo. Dan untuk mengetahui dan menganalisis apakah yang mempengaruhi fungsi efektivitas polri dalam penanggulangan tindak pidana pencurian hewan di Kabupaten Wajo. Penelitian ini adalah penelitian hukum dengan tipe penelitian empiris, yaitu suatu metode penelitian hukum yang berfungsi untuk melihat hukum dalam artian nyata dan meneliti bagaimana bekerjanya hukum di lingkungan masyarakat. Adapun data yang digunakan dalam penelitian ini meliputi data primer, data dan bahan. Adapun teknik pengumpulan data hukum dalam penelitian ini dilakukan dengan wawancara dan qisioner. Hasil penelitian ini menjelaskan tentang Evektivitas fungsi Polri dalam penaggulangan tindak pidana pencurian hewan di Kabupaten Wajo, telah berjalan secara cukup efektif, meskipun masih terdapat ruang untuk peningkatan. Keberhasilan penanganan ke depan sangat bergantung pada sinergi yang lebih kuat antara kepolisian, pemerintah daerah, dan masyarakat dalam membangun sistem keamanan lingkungan yang berbasis pada pencegahan, pemantauan, dan respons cepat terhadap setiap potensi gangguan, khususnya di sektor peternakan. Dan faktor yang mempengaruhi efektivitas fungsi Polri dalam menangani tindak pidana pencurian hewan di Kabupaten Wajo terdapat sejumlah faktor utama, yakni sarana prasarana, kompetensi teknis aparat, partisipasi masyarakat, dukungan pemerintah daerah, kondisi geografis, hambatan pembuktian hukum, serta budaya hukum masyarakat. Diharapkan agar pihak kepolisian lebih meningkatkan patroli di wilayah rawan pencurian hewan. Selain itu, penting untuk membentuk satuan tugas atau tim khusus yang fokus menangani tindak pidana pencurian hewan, agar proses penyelidikan bisa berjalan lebih cepat dan efektif. Serta diharapkan Polri lebih aktif membangun kerja sama dengan masyarakat melalui kegiatan penyuluhan hukum dan penguatan sistem keamanan lingkungan dan dukungan dari pemerintah daerah.